Digitalization of Financial Inclusion: Implementation of QRIS to Support the Resilience of SMEs in Tasikmalaya City - Evilia Sri Yuniar; Nita Fauziah Oktaviani (Pattimura University, 2026)
One of the main challenges faced by MSMEs is limited access to formal financial services. Many MSMEs still rely on cash transactions, do not have bank accounts, and have difficulty obtaining productive loans. This condition reflects the low level of financial inclusion, which ultimately limits the ability of MSMEs to survive and grow. The purpose of this study is to develop SMEs through digitalization of financial inclusion to support the resilience of SMEs in Tasikmalaya City. The research method used is a quantitative approach with Structural Equation Modeling analysis based on Partial Least Square (SEM-PLS) with the SmartPLS4 tool. The results show that QRIS influences Digital Financial Inclusion, QRIS influences SME Resilience, QRIS is able to mediate digital financial inclusion on SME resilience and QRIS moderates (strengthens) digital financial inclusion in supporting the resilience of SMEs in Tasikmalaya City. QRIS plays a role in expanding financial access for SMEs in Tasikmalaya City, so that in its implementation, QRIS is used as a payment diversification, expanding the market and maintaining income stability as a resilience strategy for SMEs in Tasikmalaya City.